Effects of Chronic Administration of Zonisamide, an Antiepileptic Drug, on Bone Mineral Density and Their Prevention With Alfacalcidol in Growing Rats - Atsushi Takahashi; Kenji Onodera; Junzo Kamei; Shinobu Sakurada; Hisashi Shinoda; Shuichi Miyazaki; Takashi Saito; Hideaki Mayanagi (Elsevier, 2003)
We investigated the effects of chronic administration of zonisamide, an antiepileptic agent, on bone metabolism in growing rats. Administration of zonisamide at a dose of 80 mg/kg per day, s.c. for 5 weeks significantly decreased bone mineral density (BMD) at the tibial metaphysis and the diaphysis. The percent rate of decrease in BMD at the tibial metaphysis and the tibial diaphysis was 9.2% and 5.0%, respectively. There was no significant difference between these groups in the growth of the rats. Treatment with zonisamide at a dose of 80 mg/kg increased serum pyridinoline level, a marker of bone resorption, while it does not affect the serum intact osteocalcin level, a marker of bone formation. Combined administration of alfacalcidol, an active vitamin D3 metabolite, at a dose of 0.1 μg/kg per day with zonisamide prevented a decrease in BMD and showed an increase of serum pyridinoline levels. These results suggest that zonisamide may cause bone loss by accelerating bone resorption rather than inhibiting bone formation. Moreover, the bone loss induced by zonisamide could be prevented by combining zonisamide with alfacalcidol.